The impact of trade shock exposure on child labor and schooling in Brazil - Viaro, Arthur Augusto (2017)
Child labor is still a relevant problem in developing countries and understanding the way that households respond in terms of children\'s time allocation to labor market incentives has relevant policy implications. In this paper, I explore a plausibly exogenous trade-induced labor market shock to assess how changes in returns to work affect children\'s time allocation in Brazil. To provide a good proxy for distinctly exogenous changes to the returns to adult labor as well as returns to the child labor I propose a strategy that distinguish between employment shocks that differentially affect adults and children. The results suggest an asymmetric impact on household decisions about children\'s time allocation that depend upon the source of the shock. First, larger import competition shocks concentrated on adult workers decrease the share of children that attend school, while an adverse shock concentrated on child workers has a positive effect on schooling, but the estimates are not statistically significant. On the other hand, both shocks decrease the share of working children. However, shocks on adults increase idleness, while shocks on children increase full-time schooling. I provide evidence that poverty and employment composition pattern are two possible mechanisms behind the results. I also find that adverse shocks on children have positive effects on math scores in a standardized national exam (Saeb) and stronger effects for children living in rural areas.